2010
DOI: 10.3727/096368910x508807
|View full text |Cite
|
Sign up to set email alerts
|

Seventy-Two-Hour Preservation, Resuscitation, and Transplantation of an Isolated Rat Heart with High Partial Pressure Carbon Monoxide Gas (PCO = 400 hPa) and High Partial Pressure Carbon Dioxide (PCO2 = 100 hPa)

Abstract: The cardiac cavity of an isolated rat heart was filled with a Krebs-Henseleit (KH) solution, and the heart was hung in a high-pressure chamber. After the high-pressure chamber had been filled with a mixed gas (PCO = 400 hPa, PCO(2) = 100 hPa, PO(2) = 900 hPa, PHe = 5600 hPa) and preserved for 72 h, we performed a cervical ectopic heart transplantation on a recipient rat and resuscitated the preserved heart. This is the first incidence in the world of a mammalian organ having been successfully preserved and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Previous studies have reported successful organ preservation using a high-pressure chamber filled with a mixed gas in a cervical ectopic heart transplantation model. 7,10,11 Here, we evaluated long-term graft function after preserving the graft using this method in a rat kidney transplantation model as a life-supporting model. CO has anti-inflammatory and anti-apoptotic effects and has attracted attention as a medical gas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported successful organ preservation using a high-pressure chamber filled with a mixed gas in a cervical ectopic heart transplantation model. 7,10,11 Here, we evaluated long-term graft function after preserving the graft using this method in a rat kidney transplantation model as a life-supporting model. CO has anti-inflammatory and anti-apoptotic effects and has attracted attention as a medical gas.…”
Section: Discussionmentioning
confidence: 99%
“…Miyamoto et al (12) looked at the improved attachment capability of cryopreserved human hepatocytes with the use of a highly proteinaceous molecule, sericin. One paper studied ways to protect isolated rat hearts using high partial pressure carbon monoxide gas and carbon dioxide (2), while another looked at the renal protective effect of erythropoietin (13). Kusaka et al (10) looked at the serum tissue inhibitor of metalloproteinases 1 as a useful predictor for renal recovery from delayed graft function.…”
mentioning
confidence: 99%